Analisis Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas untuk Pengendalian Internal pada Showroom Sekoto Putro - Putri Setyo Andini; Erna Puspita; Sigit Puji Winarko (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the application of accounting information systems in cash receipts and expenditures and assess their contribution to the effectiveness of internal control at the Sekoto Putro Showroom in Kediri. The research methodology employed is a qualitative approach, with data gathered through interviews, observations, and documentation. The findings reveal that the current accounting information system is still manual and lacks standard operating procedures (SOPs). The process of cash receipt and disbursement is managed by the finance department under the direct supervision of the owner, who also functions as the primary controller. The owner’s consent is required for all large transactions, and internal control is implemented informally through cash checks and transaction authorizations. However, there are notable weaknesses, including the absence of a clear separation of duties and a lack of a well-documented recording and authorization system. These weaknesses pose risks to the efficiency and reliability of financial management and internal control. Consequently, this study recommends the implementation of a computer-based accounting system, the creation of written SOPs, and a more defined separation of financial duties. Such changes are expected to enhance the effectiveness of internal control, improve operational efficiency, ensure more accurate record-keeping, and minimize the risk of financial losses in showroom cash management. By transitioning to a formalized and computerized system, the showroom can streamline its processes and safeguard its financial resources, ensuring long-term sustainability and growth. This research highlights the need for modernizing accounting practices to foster better financial governance and strengthen internal controls in small to medium-sized businesses.